IEEE International Conference on Robotics and Automation, 2004. Proceedings. ICRA '04. 2004 2004
DOI: 10.1109/robot.2004.1307225
|View full text |Cite
|
Sign up to set email alerts
|

Classifier fusion for outdoor obstacle detection

Abstract: This paper describes an approach for using several levels of data fusion in the domain of autonomous off-road navigation. We are focusing on outdoor obstacle detection, and we present techniques that leverage on data fusion and machine learning for increasing the reliability of obstacle detection systems. We are combining color and infrared (IR) imagery with range information from a laser range finder. We show that in addition to fusing data at the pixel level, performing high level classifier fusion is benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 16 publications
0
55
0
Order By: Relevance
“…Kelly et al has demonstrated the effectiveness of multispectral imaging, specifically at the near-infrared range, for terrain classification (Kelly et al, 2004). Dima et al has employed the LUV color space and computed distribution statistics of each channel over ground patches as color features (Dima et al, 2004).…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Kelly et al has demonstrated the effectiveness of multispectral imaging, specifically at the near-infrared range, for terrain classification (Kelly et al, 2004). Dima et al has employed the LUV color space and computed distribution statistics of each channel over ground patches as color features (Dima et al, 2004).…”
Section: Related Workmentioning
confidence: 99%
“…Ramussen (2001) used Gabor filters to detect "denseness" of textured surfaces to distinguish roads from surrounding vegetation. Dima employed a Fast Fourier Transform representation of terrain surfaces for texture feature extraction (Dima et al, 2004). Angelova utilized a histogram-based method where terrain classes are represented by textons and terrain patches are identified through occurrence statistics of these textons .…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the inherent difficulties in understanding natural objects and changing environments, autonomous driving is still in its infancy. However, existing results such as motion planning with 3D vision and the use of multiple classifiers [10], [14] shed light on a different class of problems, where roads do not disappear completely.…”
Section: Related Workmentioning
confidence: 99%
“…Motion blurring and vibration caused by a fast moving vehicle further degrade image quality. To address these issues, researchers approach the problem using different strategies such as color vision [10], [16], prior knowledge [6], pixel voting [15], classifier fusion [14], optical flow [21], neural networks [3], and machine learning [20], [21].…”
Section: Related Workmentioning
confidence: 99%